Pengaruh Variasi Ketinggian Chamber pada Proses Gas Atomisasi dengan Nozel 45° terhadap Distribusi Ukuran Serbuk ADC12 - Pawawoi Pawawoi; Ressy Noor Rafiq; Besse Titing Karmiati; Naufal Dhiya'ulhaq; Sabrina Maharani Julanov (Universitas Sarjanawiyata Tamansiswa, 2026)
The gas atomization process is widely used to produce aluminum alloy powder with controlled particle size distribution and morphology. This study aims to analyze the effect of variations in the height of the atomization chamber (80 cm, 120 cm, and 160 cm) in the gas atomization process using a fixed nozzle at a 45° angle on the size distribution of ADC12 powder. ADC12 alloy was melted at 750 °C, then atomized using compressed air at a pressure of 8 bar and argon gas at a pressure of 20 bar. The results showed that variations in the height of the atomization chamber affected the powder production efficiency and particle size distribution. The powder production efficiency was in the range of 76.72%–98.95%, with the highest value at a height of 80 cm. Changes in the height of the atomization chamber affected the droplet flight time and solidification behavior, resulting in differences in particle size distribution. The fraction of powder <100 µm was only 0.99%, indicating the limitation of fine particle formation under the process conditions used. Morphological analysis using SEM showed spherical, tear drop, rounded, dan irregular shaped particles, with the dominant spherical particles in the size range of 60.7–95.3 µm. These results confirm that the height of the atomization chamber plays an important role in controlling the dynamics of fragmentation and solidification of droplets during the ADC12 gas atomization process with a 45° nozzle.